Evaluation of leukocyte depletion of packed red blood cells for the prevention of clinically observed transfusion reactions at a medical center in Eastern Taiwan - Kai-Yun Su; Jing-Chun Huang; Jing-Yi Lin; Chun-Chun Chang (Tzu Chi Medical Journal)
Objectives: The incidence of febrile nonhemolytic transfusion reactions (FNHTRs) is correlated with the level of cytokines released by donor leukocytes in blood bags during storage, which is the most common transfusion reaction. The study aimed to reveal whether the use of leukocyte-poor red blood cells (LPRBCs) can reduce the incidence of transfusion reactions to promote patient safety. Materials and Methods: From January 2014 to June 2022, 158,122 blood transfusion reports were collected from a medical center in Eastern Taiwan. Data were categorized into three groups according to usage: prepromotion use of LPRBCs (January 2014–April 2016), promotion use of LPRBCs (May 2016 to February 2018), and full utilization of LPRBCs (March 2018 to June 2022). According to the American Association of Blood Bank Common Transfusion Reaction Reporting Form version 2.0 reporting system, FNHTRs were classified as moderate transfusion reactions. We used these data to analyze the association between LPRBC use and transfusion reaction rate. Results: At our hospital, the LPRBC usage rate from January 2014 to April 2016, May 2016 to February 2018, and March 2018 to June 2022 was 5.37%, 34.82%, and 56.45%, respectively. The total transfusion reaction rate from January 2014 to April 2016 was 1.66%, whereas the moderate reaction rate was 1.29%. The total transfusion and moderate reaction rates from May 2016 to February 2018 were 1.41% and 1.00%, whereas those from March 2018 to June 2022 were 0.95% and 0.63%, respectively. The total transfusion and moderate reaction rates from March 2018 to June 2022 decreased by 42.8% and 51.2%, respectively, compared with those from January 2014 to April 2016. We further compared the incidence of transfusion reactions caused by packed red blood cells (PRBC) and LPRBC products in different years. The results showed that between 2014 and 2022, the types of blood transfusion reaction caused using PRBC and LPRBC products are the mild transfusion reaction rate of 0.20%/0.20%, the moderate transfusion reaction rate of 1.61%/0.69%, the severe transfusion reaction rates 0.38%/0.16%, and the total transfusion reaction rates 2.19%/1.05%. Conclusion: Our study results indicate that both total transfusion and moderate reaction rates significantly decreased with increasing LPRBC usage rate. Based on our data analysis, LPRBC is more effective in reducing moderate and severe transfusion reactions than PRBC.